Inflation risks and inflation risk premia - Juan Angel García; Thomas Werner (European Central Bank (ECB), 2010)
This paper investigates the link between the perceived inflation risks in macroeconomic forecasts and the inflation risk premia embodied in financial instruments. We first provide some stylized facts about the term structure of inflation compensation, inflation expectations and inflation risk premia in the euro area bond market. Latent factor models like ours fit data well, but are often critisized for lacking economic interpretation. Using survey inflation risks, we show that perceived asymmetries in inflation risks help interpret the dynamics of long-term inflation risk premia, even after controlling for a large number of macro and financial factors.
Keywords: G12; E31; E43; 330; Affine term structure models; inflation compensation; inflation risk; inflation risk premia; inflation risks; state-space modelling; Inflation; Risikoprämie; Zinsstruktur; Zustandsraummodell